Environmental Costs Versus Sustainable Business Development - Khatoon, Asma; Jain , Garima; Abdelraheem, Abubkr Ahmed Elhadi; Khan, Imran Ahmad (International Journal of Accounting and Economics Studies, 2025)
The need for companies to value, measure and disclose environmental impacts in the search to make better decisions regarding ‎environmental management in the future is evident, however, many companies decide not to recognize the environmental costs derived from ‎the development of their social object, this is largely due to the lack of knowledge of environmental accounting on the part of company ‎managers since they focus on short-term profitability, which in most cases implies an excessive consumption of resources, and not on long-‎term sustainability, which aims at a conscious consumption of these resources. Currently, due to the growing environmental deterioration, it ‎is necessary to take measures to ensure that resources are sustainable over time; therefore, it is of vital importance that companies integrate ‎environmental management policies into their operational development plans. Therefore, this article aims to provide a brief overview of the ‎role of environmental costs in the sustainable development of companies‎.
Keywords: Environmental Costs; Sustainable Development; Environmental Accounting